Effects of electromyostimulation training and volleyball practice on jumping ability - Malatesta, D.; Cattaneo, F.; Dugnani, S.; Maffiule, N. (The Journal of Strength and Conditioning Research, 2003)
The aim of this study was to investigate the influence of a 4-week electromyostimulation (EMS) training program on the vertical jump performance of 12 volleyball players. EMS sessions were incorporated into volleyball sessions 3 times weekly. EMS consisted of 20-22 concomitant stimulations of the knee extensor and plantar flexor muscles and lasted 12 minutes. No significant changes were observed after EMS training for squat jump (SJ) and counter movement jump (CMJ) performance, while the mean height and the mean power maintained during 15 seconds of consecutive CMJs significantly increased by 4% (p < 0.05). Ten days after the end of EMS training, the jumping height significantly (p < 0.05) increased compared with baseline also for single jumps (SJ +6.5%, CMJ +5.4%). When the aim of EMS resistance training is to enhance vertical jump ability, sport-specific workouts following EMS would enable the central nervous system to optimize the control to neuromuscular properties.